A arte como comunicação afetiva: experiência espiritual e a produção artística - Sekiguchi, Julio Ferreira (2011)
The purpose of this thesis is to think about artistic production – developed in holistic and integral perspective of human existence – having the spiritual experience as its main reference. The ponderations presented here result from observations which began 15 years ago, the last five years being the most significant. This work consists of researches paired with practical and theoretical studies which articulate the spiritual experience and the artistic production, describing them as lived experiences. The aim is to demonstrate through art (artistic production) the relation materiality versus immateriality existent in the world, and the possibility that – through the spiritual or creative experience, in a unified system of interior provocation equivalent to the mystical experience – the subject faces the unique dimension of freedom, which allows him/her to determine and construct his/her own destiny. This way, I believe that man’s balance towards himself, society and the environment may be reached through the spiritual and creative experiences, which need to be cultivated; and the artistic production attempts to demonstrate such possibility. As a consequence of these experiences and analyses, I collected some orientations. The most determinant are the one that establishes the creative experience and the affectionate relations as models to relate to the world and the one which understands that the creative experience is not the privilege of a selected few, but a dimension of human life which everyone has access to.